Proceedings of the 10th ACM Conference on Recommender Systems 2016
DOI: 10.1145/2959100.2959101
|View full text |Cite
|
Sign up to set email alerts
|

Recommender Systems from an Industrial and Ethical Perspective

Abstract: Over the recent years, a plethora of recommender systems (RS) have been proposed by academics. The degree of adoptability of these algorithms by industrial e-commerce platforms remains unclear. To get an insight into real-world recommendation engines, we survey more than 30 existing shopping cart solutions and compare the performance of popular recommendation algorithms on proprietary e-commerce datasets. Our results show that deployed systems rarely go beyond trivial "best seller" lists or very basic personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
(17 reference statements)
0
14
0
2
Order By: Relevance
“…This, the authors predict, could be made achievable through the use of interlinked big data structures. Finally, Paraschakis (2016Paraschakis ( , 2017Paraschakis ( , 2018 provides one of the most detailed accounts. Focusing on e-commerce applications, Paraschakis suggests that there are five ethically problematic areas:…”
Section: Inappropriate Contentmentioning
confidence: 99%
“…This, the authors predict, could be made achievable through the use of interlinked big data structures. Finally, Paraschakis (2016Paraschakis ( , 2017Paraschakis ( , 2018 provides one of the most detailed accounts. Focusing on e-commerce applications, Paraschakis suggests that there are five ethically problematic areas:…”
Section: Inappropriate Contentmentioning
confidence: 99%
“…Finally, (Paraschakis, 2016(Paraschakis, , 2017(Paraschakis, , 2018 provides one of the most detailed accounts.…”
Section: Ethical Contentmentioning
confidence: 99%
“…Furthermore, Paraschakis (2016) surveyed more than 30 current shopping cart solutions and compared the performance of popular recommendation algorithms on e-commerce data sets. Results revealed that the systems rarely go beyond trivial bestseller lists.…”
Section: Literature Reviewmentioning
confidence: 99%